Darier disease in Israel: combined evaluation of genetic and neuropsychiatric aspects. (17th December 2015) - Dodiuk‐Gad, R.P.; Cohen‐Barak, E.; Khayat, M.; Milo, H.; Amariglio‐Diskin, L.; Danial‐Faran, N.; Sah, M.; Ziv, M.; Shani‐Adir, A.; Amichai, B.; Zlotogorski, A.; Borochowitz, Z.; et al.
Summary: Background: Darier disease (DD) is a rare genodermatosis caused by heterozygous mutations in the ATP2A2 gene. It has been associated with neuropsychiatric manifestations. Objectives: To investigate the genetic basis of Israeli patients with DD, and its association with the neuropsychiatric phenotype. Methods: A cohort of 32 families comprising 74 affected individuals and 13 unaffected family members was recruited from the Haemek Dermatology Department and other dermatology clinics in Israel. The individuals were evaluated by detailed questionnaires, physical examination and genetic analysis. The main outcome measures were genetic mutations, psychiatric profile and their association. Results: Twenty‐three mutations in ATP2A2 were scattered over the entire gene, 14 of them novel. Two families shared the same mutation. Twenty‐one patients (28%) had a history of psychiatric disorders, most of them mood disorders. Another seven patients (9%) were highly suspected of having a psychiatric disorder; 21 (28%) reported suicidal thoughts and five (7%) had attempted suicide. The psychiatric phenotype demonstrated inter‐ and intrafamilial variability, and was not associated with disease severity, family history of psychiatric disease or mutation location. Conclusions: The cohort demonstrated genetic heterogeneity with no mutation cluster along the gene, and a high prevalence of psychiatric disorders. Although no clear genotype–phenotype correlation was found, the results point to a major effect of genetic background on psychiatric phenotype, together with other modifiers. Abstract : What's already known about this topic? Darier disease, a rare genodermatosis, has been associated with a neuropsychiatric phenotype. The origin of the association is unknown. What does this study add? A genetic mutation in ATP2A2 exposes patients with Darier disease to risk of psychiatric manifestations. This is independent of the mutation's location, the severity of skin disease or a family history of psychiatric illness. Linked Comment: Kamijo. Br J Dermatol 2016;174: 488–489 .